Pharmacogenetic considerations for late life depression therapy - Pitychoutis, P M; Kokras, N; Sanoudou, D.; Dalla, C; Papadopoulou-Daifoti, Z. (Expert Opin Drug Metab ToxicolExpert Opin Drug Metab ToxicolExpert Opin Drug Metab Toxicol, 2013)
INTRODUCTION: Geriatric depression is a heterogeneous disorder with a complex genetic background. Current first-line treatment of depression is associated with a lower therapeutic outcome in aged depressed patients, when compared to younger subjects. Research which has explored this inadequate response has highlighted several factors which have come into play with the pharmacogenetics of antidepressants in the elderly being a particular area of interest. AREAS COVERED: The authors perform a critical review of the English language articles from PubMed using search terms such as late-life/geriatric depression, antidepressants, pharmacogenetics, pharmacogenomics, pharmacokinetic, genetic, genotype, remission, therapy, treatment and polymorphism. EXPERT OPINION: The emerging clinical and pharmacogenetic data are slowly unveiling the importance of the genome - age interaction in antidepressant response. This data introduces a critical new parameter in personalized medicine. A profound analysis of the age factor in the pharmacogenetics of antidepressant response is imperative, in order to elucidate the clinical significance of these findings and thereby improve patient treatment in the elderly.
Keywords: *Pharmacogenetics; Aged, 80 and over; Antidepressive Agents/adverse effects/pharmacokinetics; Depression/*drug therapy/*genetics; Genotype; Geriatric Assessment; Humans; Precision Medicine; Treatment Outcome